Tumor necrosis factor-alpha inhibitors suppress CCL2 chemokine in monocytes via epigenetic modification. (March 2017) - Lin, Yi-Ching; Lin, Yu-Chih; Huang, Ming-Yii; Kuo, Po-Lin; Wu, Cheng-Chin; Lee, Min-Sheng; Hsieh, Chong-Chao; Kuo, Hsuan-Fu; Kuo, Chang-Hung; Tsai, Wen-Chan; Hung, Chih-Hsing
Graphical abstract: Highlights: TNF-α inhibitors suppress CCL2 production in human monocytes. TNF-α inhibitors suppress CCL2 through MAPK and p65-NFκB pathways. TNF-α inhibitors downregulate the histone acetylation in the CCL2 promoter. TNF-α inhibitors downregulate the histone trimethylation in the CCL2 promoter. Abstract: The treatment of rheumatoid arthritis (RA) with tumor necrosis factor-alpha (TNF-α) inhibitors could lead to adverse effects. Therefore, the identification of downstream therapeutic targets is important. Monocyte chemoattractant protein-1 (MCP-1, also called CCL2) is related to RA disease activity, and epigenetic modifications are hypothesized to regulate gene expression in RA pathogenesis. We studied the effects of two TNF-α inhibitors, etanercept and adalimumab, on CCL2 expression and the potentially associated intracellular mechanisms, including epigenetic regulation. Etanercept and adalimumab decreased CCL2 production in THP-1 cells and human primary monocytes, as detected using enzyme-linked immunosorbent assays, and these changes in the CCL2 levels were independent of the TNF-α levels. Etanercept and adalimumab suppressed mitogen-activated protein kinase (MAPK) phospho-p38, phospho-JNK, phospho-ERK and nuclear factor-κB (NF-κB) phospho-p65, as demonstrated using western blot analyses. The investigation of epigenetic modifications using chromatin immunoprecipitation revealed that etanercept and adalimumab down-regulated acetylation of histone (H)3 and H4 in the CCL2 promoter region by decreasing the recruitment of the NF-κB associated acetyltransferases p300, CBP and PCAF. Etanercept and adalimumab also down-regulated trimethylation of H3K4, H3K27, H3K36 and H3K79 in the CCL2 promoter region by decreasing the expression of the related methyltransferases WDR5 and Smyd2. We demonstrated that TNF-α inhibitors exert immunomodulatory effects on CCL2 expression in human monocytes via MAPKs, NF-κB and epigenetic modifications. These findings broaden the mechanistic knowledge related to TNF-α inhibitors and provide novel therapeutic targets for RA.